AN ANALYSIS OF SETTING IN FAST FURIOUS MOVIE - I Komang Adi Sokantara; I Made Yogi Marantika (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study is entitled an Analysis of Setting in Fast Furious Movie. It is aimed at analyzing the types of setting and how setting constructs the plot used observation method. The data source of this  study was Fast and Furious Movie. The theories used to determine the problems proposed by Kenney (1966) with the book entitled “How to Analyse Fiction”. Based on Kenney’s theory, setting can be divided into two types namely neutral setting and spiritual setting. The element of neutral setting consists of setting of place, setting of time and setting of environments. Based on the analysis of the first problem, there were three types of settings such as setting of places was found 10 (56%), setting of time was found 3 (17%) and setting of environments was found 5 (28%). Those could be classified as neutral settings. Then, based on the analysis of the second problems, it can be concluded that the data for construction of plot there were 4 types found for constructing the plot such as exposition was found 2 (20%) it was when Dom lives in new life and when he told his old lives situation, complication was found 2 (20%) it was when Dom got a job and when he accidently accepted a new mission, climax was found 4 (40%) it was when Dom fight with the Military team, Dom knowing his brother Jackob, Dom’s team want to broke the satellite, Jackob was fail and resolution was found 2 (20%) it was when Jackob back to his brother and dinner to clear the problem through Dom and Jackob.